The Amish quiltmaker's uninvited guest - Beckstrand, Jennifer (Beckstrand, Jennifer. Amish quiltmaker., 2024)
"Esther's distant cousin, widower Menno Eicher, needs to be hard-headed and practical. Swamped by family and farm responsibilities, he must find the perfect wife as quickly as possible, so he's shown up in Colorado--with "finding a wife" on his To-Do list! Esther's community has many women who could match his ever-growing requirements. Still, after a chance meeting, Menno keeps coming back to baker Joanna Yoder. Hard-working, honest, and forthright, she's distracting Menno from his search, opening his heart--yet refuses to believe he's falling hopelessly in love with her... Happily busy inventing and selling delicious desserts, Joanna has no time for someone as ridiculously exacting as Menno. After all, what sort of man thinks choosing a wife is like picking a pie at the general store? But she soon sees the surprisingly kind heart, doting father, and understanding man beneath his hard-to-please ways. With faith and genuine love, might the few things they have in common overcome the differences between them--and prove precious enough to risk a future together?"--